Impact of the COVID-19 pandemic on long-term trends in the prevalence of diabetic ketoacidosis at diagnosis of paediatric type 1 diabetes: an international multicentre study based on data from 13 national diabetes registries. Issue 11 (November 2022) - Birkebaek, Niels H; Kamrath, Clemens; Grimsmann, Julia M; Aakesson, Karin; Cherubini, Valentino; Dovc, Klemen; de Beaufort, Carine; Alonso, Guy T; Gregory, John W; White, Mary; Skrivarhaug, Torild; Sumnik, Zdenek; et al.
Summary: Background: An increased prevalence of diabetic ketoacidosis at diagnosis of type 1 diabetes in children was observed in various diabetes centres worldwide during the COVID-19 pandemic. We aimed to evaluate trends in the prevalence of diabetic ketoacidosis at diagnosis of paediatric type 1 diabetes before and during the COVID-19 pandemic, and to identify potential predictors of changes in diabetic ketoacidosis prevalence during the pandemic. Methods: For this international multicentre study, we used data from 13 national diabetes registries (Australia, Austria, Czechia, Denmark, Germany, Italy, Luxembourg, New Zealand, Norway, Slovenia, Sweden, USA [Colorado], and Wales). The study population comprised 104 290 children and adolescents aged 6 months to younger than 18 years, who were diagnosed with type 1 diabetes between Jan 1, 2006, and Dec 31, 2021. The observed diabetic ketoacidosis prevalence in 2020 and 2021 was compared to predictions based on trends over the pre-pandemic years 2006–19. Associations between changes in diabetic ketoacidosis prevalence and the severity of the COVID-19 pandemic and containment measures were examined with excess all-cause mortality in the whole population and the Stringency Index from the Oxford COVID-19 Government Response Tracker. Findings: 87 228 children and adolescents were diagnosed with type 1 diabetes between 2006 and 2019, 8209 were diagnosed in 2020, and 8853 were diagnosed in 2021. From 2006 to 2019, diabetic ketoacidosis at diagnosis of type 1 diabetes was present in 23 775 (27·3%) of 87 228 individuals and the mean annual increase in the prevalence of diabetic ketoacidosis in the total cohort from 2006 to 2019 was 1·6% (95% CI 1·3 to 1·9). The adjusted observed prevalence of diabetic ketoacidosis at diagnosis of type 1 diabetes was 39·4% (95% CI 34·0 to 45·6) in 2020 and 38·9% (33·6 to 45·0) in 2021, significantly higher than the predicted prevalence of 32·5% (27·8 to 37·9) for 2020 and 33·0% (28·3 to 38·5) for 2021 (p<0·0001 for both years). The prevalence of diabetic ketoacidosis was associated with the pandemic containment measures, with an estimated risk ratio of 1·037 (95% CI 1·024 to 1·051; p<0·0001) per ten-unit increase in the Stringency Index for 2020 and 1·028 (1·009 to 1·047; p=0·0033) for 2021, but was not significantly associated with excess all-cause mortality. Interpretation: During the COVID-19 pandemic, there was a marked exacerbation of the pre-existing increase in diabetic ketoacidosis prevalence at diagnosis of type 1 diabetes in children. This finding highlights the need for early and timely diagnosis of type 1 diabetes in children and adolescents. Funding: German Federal Ministry for Education and Research, German Robert Koch Institute, German Diabetes Association, German Diabetes Foundation, Slovenian Research Agency, Welsh Government, Central Denmark Region, and Swedish Association of Local Authorities and Regions.